Alat Pelindung Diri, Pengetahu Perilaku Penggunaan Alat Pelindung Diri (APD) Pekerja di Industri Tripleks CV Tumitah - Rahmi, Annisa; Kasjono, Heru Subaris; Sugianto (Poltekkes Kemenkes Bengkulu, 2025)
Background: The implementation of Occupational Health and Safety (OHS) aims to minimize the risk of workplace accidents. The use of Personal Protective Equipment (PPE) is an essential part of accident prevention efforts, especially in industrial environments. However, unsynchronized between safety policies and the actual behavior of workers in using PPE are still frequently found. Purpose: Observe the behavior of PPE usage among workers in the plywood industry at CV Tumitah, including their level of knowledge, attitudes, practices, and reasons for incomplete PPE usage. Methods: The study was designed by descriptive with 48 respondents selected by proportional random sampling. Data were collected through questionnaires to assess knowledge and attitudes, and observations using a checklist to evaluate PPE usage practices. Results: The majority of workers had a good level of knowledge (96%), all respondents showed a positive attitude (100%), and all were found to use PPE incompletely (100%). The main reasons for not using PPE were discomfort, unequal distribution, and the unavailability of specific PPE such as helmets and safety shoes. Conclusion: The workers’ level of knowledge was categorized as good, their attitudes were positive, but the practice of PPE usage remained incomplete.